Increasing Basic Knowledge of Students with the Inquiry Learning Model on the Nature of Change of Material in the Form of Objects with the Aid of Game Quizizz/ Meningkatkan Pengetahuan Dasar Mahasiswa dengan Model Pembelajaran Inkuiri - Maylana Nurfariha; Nirwana Anas; Siti Fatonah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
This research was conducted to know the extent to which students have reached their basic knowledge because, if it is too late, it will become a risk for evaluation and improvement in the future. They also will find it difficult when teaching their students later. The purpose of this study was to determine the implementation of the inquiry learning model and the student's basic knowledge about the material "the nature and change of object form" with the Quizizz game. Researchers used qualitative research methods with a descriptive approach. Data analysis used the model of Matthew B. Milles A. Michael Huberman which consisted of data reduction, data presentation, and conclusion drawing. From the results of the study, the implementation of the inquiry learning model on the material "the nature of change in the shape of objects" has six stages, namely, the lecturer prepares RPS and LKPD, while students raise questions, conduct experiments, and observations, explain the results of observations, and do quizzes using "Quizizz games". The Quizizz game has 15 questions, with a sample of 23 PGMI students. After applying the inquiry learning model, the basic knowledge of PGMI students whose scores are above 80% are 19 students, and those below 80% are four students. This is based on the data obtained by the researchers from the student Quizizz game scores. So, it can be concluded that in the implementation of the inquiry learning model, Quizizz games can be used as a supporting medium to determine the basic knowledge of students about the nature of change in the shape of objects. Abstrak Penelitian ini dilakukan untuk mengetahui sejauh mana pentingnya pengetahuan dasar mahasiswa karena, jika hal ini terlambat diketahui, ini akan berdampak pada evaluasi dan perbaikan di kemudian hari. Mereka juga kesulitan ketika mengajar siswa-siswi nantinya. Tujuan penelitian ini untuk mengetahui implementasi model pembelajaran inkuiri pada materi “sifat dan perubahan wujud benda” berbantuan game Quizizz dan pengaruhnya terhadap pengetahuan dasar mahasiswa. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Analisis data menggunakan model Mattew B. Milles A. Michael Huberman yang terdiri atas reduksi data, penyajian data, dan penarikan kesimpulan. Dari hasil penelitian implementasi model pembelajaran inkuiri pada materi sifat perubahan wujud benda terdapat enam tahapan, yaitu dosen menyiapkan RPS dan LKPD, mahasiswa membuat pertanyaan, melakukan percobaan, pengamatan, memaparkan hasil pengamatan, dan mengerjakan kuis menggunakan game Quizizz. Game Quizizz terdiri dari 15 butir soal, dengan sampel 23 mahasiswa PGMI. Setelah diterapkan model pembelajaran inkuiri, skor pengetahuan dasar mahasiswa PGMI diatas 80% ada 19 mahasiswa dan dibawah 80% ada empat mahasiswa. Hal ini berdasarkan pada data yang didapatkan dari skor game Quizizz mahasiswa. Karena itu disimpulkan bahwa implementasi model pembelajaran inkuiri berbantuan game Quizizz dapat digunakan sebagai media pendukung untuk mengetahui pengetahuan dasar mahasiswa mengenai sifat perubahan wujud benda.